Perturbed Sierpinski carpet resonator and its usage in compact dual and triple band bandpass filters. Issue 5 (17th February 2016) - Pal, Manimala; Ghatak, Rowdra; Sarkar, Pankaj
ABSTRACT: In this paper, perturbed Sierpinski carpet fractal shaped resonator is characterized and applied in the design of multiband band pass filters (BPFs). The route to achieving compact multimode resonators starting from the Sierpinski carpet fractal shaped resonator is detailed. The proposed resonators are used to demonstrate two topologies of dual band bandpass filters with passband center frequencies at 3.5 GHz as well as 5.5 GHz, respectively. Both the designs exhibit nearly identical passband bandwidth. In the second design, it is observed that the second passband gets slightly shifted towards 5.85 GHz. However, with edge loading this shift is nullified. A scaled down version of the same resonator is designed and three such resonators are interdigitally coupled in conjunction with complementary split ring resonators to exhibit a novel technique of achieving compact triband bandpass filter. All designs have acceptable passband insertion loss in the respective bands. Accessories are used to improve passband selectivity in all designs and also a wide stop band till 10 GHz is obtained. Fabrication prototypes for all the variants are realized with simulated and measured results in good agreement. © 2016 Wiley Periodicals, Inc. Int J RF and Microwave CAE 26:418–425, 2016.